Modeling the hygrothermal creep behavior of wood plastic composite (WPC) lumber made from thermally modified wood. (August 2020) - Alrubaie, Murtada Abass A; Lopez-Anido, Roberto A; Gardner, Douglas J; Tajvidi, Mehdi; Han, Yousoo
The viscoelastic behavior of an extruded wood plastic composite (WPC) made from thermally modified wood under hygrothermal treatment was studied and modeled. Multiple three-point bending creep/recovery tests were carried out using a dynamic mechanical thermal analyzer (DMTA) equipped with a submersible clamp. WPC specimens with a 15-mm span were subjected to two initial applied stresses; 9% and 14% of the flexural strength in 30 min of creep and 30 min of creep recovery under the combined effects of temperature (25°C, 35°C, and 45°C) and water immersion (saltwater (SW) and distilled water). A dry condition WPC control was used to compare the hygrothermal effects with respect to the control conditions. The WPC material in this article exhibited a linear viscoelastic behavior under the effect of temperature, whereas a nonlinear viscoelastic behavior was observed under immersion conditions. A power law model is considered a useful model to describe the creep behavior of WPC specimens with a 15-mm span in the control and the SW conditions and at 45°C. A power law model was used to describe 180-day creep deflection of WPC lumber beams with an 853-mm span subjected to 12 MPa of the flexural strength in four-point bending at 50% relative humidity and at 21°C. The power law model predicts that the WPC lumber will reach a flexural strain in outer fiber of 1% in approximately 150 years.